Effect of 1% H2O2 on Three Salivary Stress Biomarkers, Cortisol, Alpha-Amylase, and sIgA - Nantawachara Jirakittayakorn; Eakapong Tamboon; Somsak Mitrirattanakul (International Dental Journal, 2023)
BACKGROUND: Due to the COVID-19 pandemic, several associations worldwide have been recommending the use of 1% hydrogen peroxide solution as a preprocedural mouth rinse before dental treatments to reduce viral load in saliva. This protocol is also employed in stress studies, especially in the context of dental treatment that uses salivary biomarkers as an indicator. However, the effect of 1% hydrogen peroxide as mouth rinse on salivary biomarkers remains unclear. OBJECTIVE: This study aims to investigate the effects of 1% hydrogen peroxide solution as a preprocedural mouth rinse on 3 salivary stress biomarkers-salivary cortisol, salivary secretory IgA, and salivary α-amylase-both on chemical influence and mechanical irrigation. MATERIALS AND METHODS: Ninety healthy participants with confirmed negative Reverse Transcription Polymerase Chain Reaction results for COVID-19 at most 2 days prior to the experiment were included in this study. All participants were randomly allocated into 3 groups: experimental (1% hydrogen peroxide solution), positive control (distilled water), and negative control (no mouth rinse). Saliva samples were collected before and after mouth rinsing with the respective solutions. Salivary biomarkers were analysed using specific enzyme-linked immunosorbent assay kits. RESULTS: Salivary cortisol and salivary α-amylase did not significantly differ before and after rinsing, whilst salivary sIgA levels decreased in all 3 groups. Nonetheless, there were no significant differences in the changes of these biomarkers across the 3 groups. CONCLUSIONS: This study shows that using 1% hydrogen peroxide solution as a preprocedural mouth rinse for universal precaution does not alter the levels of these 3 salivary biomarkers.
Keywords: Dental Research and COVID-19; Oral microbiology and periodontitis research; Salivary Gland Disorders and Functions